New Alkaloids from Aconitum vaginatum. Issue 5 (May 2014) - Li, Juan; Chang, Hang; Zhao, Wenyu; Pi, Huifang; Ruan, Hanli; Zhang, Peng
Abstract Two new amide alkaloids, vaginatunine A and B (1 and 2, resp.), and a new C18‐diterpenoid alkaloid vaginatunine C (3), together with four known alkaloids, were isolated from the tubers of Aconitum vaginatum. Their structures were determined by means of spectroscopic analyses and comparison of the data with those reported previously.